Social capital as a BUMDes instrument in community empowerment in Sumbergondo Village, Batu City - Rafi Alfiansyah (Jurnal Sosiologi Dialektika, 2022)
BUMDes Rejeki Barokah of Sumbergondo Village in Batu City was established through a community dialectical process with the objective of resolving village issues through community empowerment. The community empowerment process can run because of the Sumbergondo BUMDes’s substantial social capital. This study aimed to reveal the reality of social capital as an instrument used by BUMDes in community empowerment in Sumbergondo Village. The method used in this study was qualitative. Data collection techniques included observation, interviews, and document studies. Putnam’s theory of social capital as the basis of the research analysis includes norms, social networks, and trust. The results indicate that BUMDes of Sumbergondo could overcome and suppress existing problems in their area, while also benefiting the surrounding community through independent waste management business units, waste banks, shops, and cafes. BUMDes of Sumbergondo is able to provide positive feedback on the social aspect by providing job vacancies, internships, and entrepreneurship training, on the environmental aspect by providing a cleaner environment, and on the economic aspect by providing additional income. It can be concluded that BUMDes are agents of social change in empowering rural communities by utilizing their social capital so that it has implications for a humanist and empowered society.